(untitled) - Traugott, Elizabeth Closs; Trousdale, Graeme (Oxford, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; This title develops an approach to language change based on construction grammar in order to reconceptualise grammaticalisation and lexicalisation. The authors show that language change proceeds by micro-steps involving every aspect of grammar including pragmatics and discourse functions
Keywords: English language -- History; Tiếng Anh -- Lịch sử; Linguistic change; Thay đổi ngôn ngữ; Construction grammar